Hemoglobin A1c as a screening strategy for gestational diabetes. Issue 3 (2018) - Schaible, Burke; Calhoun, Byron C; Bush, Stephen; Ramser, Beth; Seybold, Dara J; Broce, Mike; Fending, Philip; White, April; Williams, David L; Bracero2, Luis A
No abstract available